EFEKTIVITAS PENGGUNAAN PRAKT IKUM HERBARUIM YANG DIINTEGRASIKAN DENGAN PENDEKATAN SAINTIFIK PADA MATERI PTERIDOPHYTA (TUMBUHAN PAKU) UNTUK MENINGKATKAN PSIKOMOTORIK SISWA KELAS X DI SMA NEGERI 7 PADANGSIDIMPUAN - Lidya Putri Siregar (JURNAL EDUGENESIS, 2019)
This study aims to know whether the use of practicum herbaria which is integrated with a scientific approach has effectiveness to increase students’ psychomotor on the topic pteridophyta at the tenth grade students of SMA Negeri 7 Padangsidimpuan. The research was conducted for 3 months (April– June 2018) by applying descriptive method with 25 students as the sample and they were taken by using cluster sampling technique from 105 students. Observation was used in collecting the data. Based on descriptive analyzes, it could be found that a) the average of using practicum herbaria which is integrated with a scientific approach was 80 (very good category) and (b) level of effectiveness at the first meeting was 74.32% (effective category) and the second meeting was 92.7 % (very effective category). The average of the both meeting was 85.67% (very effective category). It is concluded the use of practicum herbaria which is integrated with a scientific approach has effectiveness to increase students’ psychomotor on the topic pteridophyta at the tenth grade students of SMA Negeri 7 Padangsidimpuan